The Effect of STEM-Based Project-Based Learning (PjBL) on Students’ Scientific Thinking Skills in Reaction Rate - Yuliana Pariyonga; Weny J.A Musa; Thayban Thayban; Lukman Abdul Rauf Laliyo; La Alio (Jambura Journal of Educational Chemistry, 2026)
Reaction rate is one of the most complex topics in chemistry and remains difficult for students to understand. This condition highlights the need for more effective instructional approaches to enhance students' scientific thinking skills.This study was conducted to analyze the effect of implementing the STEM-based Project-Based Learning (PjBL) model on the scientific thinking skills of Grade XII students in the topic of reaction rates. The research employed a quasi-experimental method using a non-equivalent control group design involving 52 students divided into an experimental class and a control class. The research instrument consisted of nine essay questions with a high level of reliability, as indicated by a Cronbach’s Alpha value of 0.740. The findings revealed that the implementation of the STEM-based PjBL model significantly enhanced students’ scientific thinking skills. This improvement was evident across all indicators measured in the experimental class, including the logical indicator, which reached 75.9%, the analytical indicator at 68.1%, the systematic indicator at 59.1%, the deductive indicator at 59.9%, and the inductive indicator, which increased to 68.1%. Furthermore, the effect size analysis yielded a score of 1.632, which falls into the very large category. Therefore, it can be concluded that the implementation of the STEM-based Project-Based Learning (PjBL) model had a very strong effect on improving students’ scientific thinking skills.